On the issue of development and state support for small and medium-sized businesses in Kazakhstan - Parmanova, R.S.; Ilasheva S.А.; Yesbolova А.Y.; Kazhmuhametova, A.A.; Dajrabaeva, A.S. (BUKETOV BUSINESS REVIEW, 2023)
Object: Study the current state of development of small and medium-sized businesses in Kazakhstan and determine the mechanisms for the formation of a system of state support for entrepreneurship, taking into account the modernization of the Kazakh economy. Methods: The following research methods were used: statistical, systemic, synthesis and analysis (economic, statistical, comparative and descriptive). Findings: the obtained results of the research made it possible to determine the peculiarities of the functioning of small and medium-sized businesses in the Republic of Kazakhstan, to assess the modern system of state support for SMEs in Kazakhstan, to develop recommendations for improving state support for SMEs. Conclusions: Issues of entrepreneurship development in Kazakhstan have a special status. A targeted and consistent business support policy is one of the main priorities of the state, since it is the SME sector that should become a key driver of further economic growth. For the effective development of the country’s economy, it is necessary to maximize the involvement of small and medium-sized businesses, because only thanks to this it is possible to achieve high indicators in all sectors of the economy and create a multi-layered market and industrial-innovative economy. However, small and medium-sized enterprises in Kazakhstan are characterized by low viability and require the development of effective measures to increase their competitiveness.